Performance Analysis Of Balinese Kulkul Beats Information System Based on Website and Android Using ISO 9126 - I Gusti Made Ngurah Desnanjaya; I Gede Iwan Sudipa; I Wayan Dani Pranata (IAES Indonesia Section, 2020)
Bali is known for its tourism and culture, the most viscous Balinese culture to date is consultation or cooperation. This can be seen from the many upakara (ceremonial) activities involving local communities, such as upakara dewa yadnya, manusia yadnya, and bhuta yadnya. In providing ceremonial information in an area in Bali, involving banjar or kulkul users. Kulkul in Bali is a traditional information medium that is still used to convey information about death, deliberation, and disaster in an area. However, people who live outside the village cannot hear information through the sound of kulkul. In this study, the Android-based Kulkul Beats Website and Information System was pre-built, but it is necessary to perform analysis of its performance testing. The system can provide information about the beat of the kulkul and is able to control the kulkul through the android app. It can also provide information about beats and will be displayed on the website, as well as controlling the kulkul through the android app. Android system testing using black box testing. From ISO 9126 test results, the functionality aspect gets a value of 1, where the function test has run 100% correctly. Test results of 100% reliability aspect test with success results. Usability test results showed 65.9% (good) results with Alpha Cronbach 0.969 (excellent). The efficiency aspect test results got a C with an average score of 77.2 and an average load time of 1.44 seconds.